Platelet Sensitivity to Prostacyclin and Thromboxane Production in Hyperlipidemic Patients - Strano, A; Davì, G; Averna, M; Rini, G B; Novo, S; Di Fede, G; Mattina, A; Notarbartolo, A (Thrombosis and Haemostasis, 1982)
In 13 type II hyperlipidemics (10 males and 3 females; mean age 50.2 ± 10.6 years), in 10 type IV hyperlipidemics (7 males and 3 females; mean age 51 ± 13.3 years) and in 23 healthy age-and sex-matched controls, the following parameters were measured: plasma cholesterol; plasma TG; plasma C-HDL; VLDL, separated in a preparative ultracentrifuge; C-LDL; Apo B, with immunoelectrophoretic method; platelet sensitivity to prostacyclin; TXB2 formation in PRP; TXB2 in serum.This study provides evidence for: 1. Reduced platelet sensitivity to prostacyclin, more evident in type II hyperlipidemia that provides an additional mechanism involved in increased platelet aggregation found in type II hyperlipidemia. 2. Enhanced TXB2 formation in PRP after thrombin stimulation (664.65 ± 142.18 pmol/108 platelets) only in type II hyperlipidemics and such enhanced formation was positively correlated to C-LDL (r = 0.53; p <0.05) and to Apo B (r = 0.62; p <0.05); serum TXB2 formation rate was also increased in type II hyperlipidemia.
Keywords: Hyperlipidemia; Thromboxane; Platelet sensitivity to prostacyclin